2022
DOI: 10.48550/arxiv.2207.13074
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Numerical relativity for Horndeski gravity

Abstract: We present an overview of recent developments in the numerical solution of Horndeski gravity theories, which are the class of all scalar-tensor theories of gravity that have second order equations of motion. We review several methods that have been used to establish well-posed initial value problems for these theories, and discuss well-posed formulations of the constraint equations. We also discuss global aspects of exact, strongly coupled solutions to some of Horndeski gravity theories: the formation of shock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 139 publications
0
9
0
Order By: Relevance
“…Here, we do not implement a method to solve the equations for general φ, but instead consider initial data for which φ = ∂ t φ = 0. With this choice of φ, the constraint equations of sGB gravity reduce to those of vacuum GR [22,23]. Even though φ = ∂ t φ =0 on the initial time slice, scalar field clouds subsequently form on a timescale that is short compared with the orbital binary timescale (within ∼ 100M 0 ).…”
Section: B Puncture Binary Black Hole Initial Datamentioning
confidence: 99%
See 4 more Smart Citations
“…Here, we do not implement a method to solve the equations for general φ, but instead consider initial data for which φ = ∂ t φ = 0. With this choice of φ, the constraint equations of sGB gravity reduce to those of vacuum GR [22,23]. Even though φ = ∂ t φ =0 on the initial time slice, scalar field clouds subsequently form on a timescale that is short compared with the orbital binary timescale (within ∼ 100M 0 ).…”
Section: B Puncture Binary Black Hole Initial Datamentioning
confidence: 99%
“…After that initial evolution time, we turn on the Gauss-Bonnet coupling λ to a non-zero value. The constraints are satisfied in this procedure, as we can think of our initial data as starting at t = 50M 0 instead, with φ = ∂ t φ = 0 and a metric field that satisfies the constraints such that the initial data satisfies the constraint equations for sGB gravity [22,23]. While we use quasi-circular initial data based on PN approximations for the initial orbital velocities from GR, we found that the scalarization process does not appreciably impact the eccentricity of our runs, and instead the eccentricity of our runs is dominated by the truncation error of the simulations.…”
Section: B Puncture Binary Black Hole Initial Datamentioning
confidence: 99%
See 3 more Smart Citations